2020
DOI: 10.21577/0103-5053.20200072
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Fluorescent Carbon-Based Dots from Waste Tire Pyrolysis

Abstract: The pyrolysis of waste tire has been proposed as an alternative route to its recycling producing residual oils that can be used as fuels. In this work, a physicochemical process to obtain carbonbased dots (CBD) from carbon black (CB L) derivatives of tires is described. For this, the CB L was treated with different acids to produce CB L1 and CB L2 particles suspension. The pH of the suspension was adjusted to 5.6 to precipitate remaining impurities. Afterwards, the supernatant was ultra-centrifuged and the yel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…As can be seen in Figure 8, all the carbon black precursors generated spherically-shaped nanoparticles. Typically, carbon dots are spherical shaped [88][89][90][91], which is in agreement with carbon dots synthesized in this study; however, it has been reported that carbon dots from waste tires synthesized by a physicochemical method was not spherically shaped and monodisperse [43].…”
Section: Preliminary Analysis Of Carbon Dotssupporting
confidence: 89%
See 2 more Smart Citations
“…As can be seen in Figure 8, all the carbon black precursors generated spherically-shaped nanoparticles. Typically, carbon dots are spherical shaped [88][89][90][91], which is in agreement with carbon dots synthesized in this study; however, it has been reported that carbon dots from waste tires synthesized by a physicochemical method was not spherically shaped and monodisperse [43].…”
Section: Preliminary Analysis Of Carbon Dotssupporting
confidence: 89%
“…Differences in the intensity of fluorescence emission were observed: a higher intensity in fluorescence emission at the range of 590 ± 35 nm in all carbon dots samples, and a higher fluorescence emission in the fraction from 0-10 kDa, regardless of the precursor. It has been previously reported that carbon dots from pyrolytic carbon black presented their maximum fluorescence signal at 415 nm [43]. In our study, the maximum fluorescence emission was observed at longer wavelengths, possibly associated with a higher oxidation degree [97,98] caused during the chemical oxidation with HNO 3 .…”
Section: Preliminary Analysis Of Carbon Dotssupporting
confidence: 65%
See 1 more Smart Citation
“…It has been reported that carbon dots from pyrolytic carbon black presented a PL peak at 415 nm at the maximum excitation wavelength (380 nm) [ 70 ]. As can be seen in Figure 10 , in our study, a bathochromic shift (shift to longer wavelengths) was observed in all carbon dot samples compared to those reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metal ions such as Hg 2+ , Au 3+ , Cr 6+ , Ag + , Fe 2+ , Cu 2+ , and Fe 3+, which are easily accumulated in animals and plants, are a significant factor that contributes to water or environmental a wide basic surface region, regardless of the form they are (Parra et al, 2020;Verma et al, 2020). Various studies on the synthesis and use of carbon quantum dots have been conducted in recent years.…”
Section: Metal Ion Detectionmentioning
confidence: 99%